IMPROVEMENT OF STUDENT PROBLEM-SOLVING ABILITIES THROUGH PROBLEM-BASED LEARNING MODELS - Rajo Hasim Lubis (ISER (Indonesian Science Education Research), 2020)
The era of digitalization requires students to always be creative so as not to be out of date, one way is to improve problem-solving abilities. This research aims to improve students' problem-solving abilities by applying a problem-based learning model. The sample used was students of class X-1 as the experimental class and class X-2 as the control class selected using simple random sampling. This type of research is a quasi-experiment and the instrument of problem-solving ability used is in the form of an essay which consists of 8 questions. The results of the study concluded that the problem-solving ability in the experimental class using the problem-based learning model was better than conventional learning